Quaternary semimagnetic Hg₁₋x₋yCdxMnySe crystals for optoelectronic application - Mazur, Yu.I.; Tarasov, G.G.; Kuzmenko, E.V.; Belyaev, A.E.; Hoerstel, W.; Kraak, W.; Masselink, W.T. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The peculiarities of the exchange interaction between the carrier spin and localized spin moments of magnetic ions in the close vicinity of semimetal-semiconductor transition have been studied on the example of semimagnetic quaternary solid solution Hg₁₋x₋yCdxMnySe (x = 0.10, y = 0.02, Eg = 45 meV) by means of Shubnikov-de Haas oscillations. It is shown that due to the s-p hybridization of electron wavefunctions the exchange constant α turns out in α complicated function of energy gap Eg and electron concentration which changes from positive αN₀ = 0.15 eV to negative αN₀ = -0.28 eV values which are typically accepted for wide gap semimagnetic semiconductors.